Single‐Molecule Magnetism in Three Dy2 Complexes from the Use of a Pentadentate Schiff Base Ligand and Different Benzoates. Issue 16 (24th July 2019) - Ge, Yu; Li, Dawei; Wang, Guoqing; Cui, Yanfeng; Najib, Muhammad Saleem; Li, Yahong; Wang, Bao‐Lin
Abstract: Three dinuclear dysprosium(III) complexes, [Dy2 L2 (O2 CPh)2 ]⋅2 MeOH (1 ), [Dy2 L2 {(2‐NO2 )O2 CPh}2 ] (2 ), and [Dy2 L2 {(2‐OH)O2 CPh}2 ]⋅ MeOH⋅ MeCN (3 ) (H2 L= N 1, N 3 ‐bis(4‐chlorosalicyladehyde)diethylenetriamine), have been synthesized and structurally characterized. Complexes1 –3 possess similar Ln2 cores and differ in substituents at the benzyl rings of benzoates. Direct current (dc) magnetic susceptibility studies in the 2–300 K range showed weak antiferromagnetic interactions between two dysprosium(III) ions in1 –3 . The alternating current (ac) magnetic susceptibility measurements indicated that they all exhibited SMM behavior. The strategic attachment of the −NO2 group (in2 ) and the −OH functionality (in3 ) on the skeleton of the benzoic acid led to subtle variations of the bond lengths and bond angles in the coordination environments of the central dysprosium(III) ions, consequently resulting in the enhancement of the energy barriers for2 and3 . Complete‐active‐space self‐consistent field (CASSCF) calculations were employed to rationalize the experimental outcomes. Theoretical calculations confirm the existence of antiferromagnetic interactions in1 –3, and the calculated dc magnetic susceptibility data agree well with those obtained experimentally. The computational results reveal more axial g tensors, as well as higher first excited Kramers doublets in2 and3 ; thus resulting in higher energy barriers in compounds2 and3 . Abstract : Overcoming barriers to attraction : The synthesis and characterization of three Dy2 single‐molecule magnets is described. The three complexes, [Dy2 L2 (O2 CPh)2 ]⋅2 MeOH, [Dy2 L2 {(2‐NO2 )O2 CPh}2 ], and [Dy2 L2 {(2‐OH)O2 CPh}2 ]⋅ MeOH⋅ MeCN (H2 L= N 1, N 3 ‐bis(4‐chlorosalicyladehyde)diethylenetriamine), possess similar Ln2 cores and differ in substituents at the benzyl rings of benzoates, which leads to modulation of the energy barriers (see figure).